Aceh Maritime Museum Design in Banda Aceh - Maulidy, Muhammad; Aini, Qurratul (Department of Architecture, Faculty of Engineering, University of Muhammadiyah Aceh, 2023)
The development of the cultural and historical heritage of the Acehnese people is in line with maritime events in the past. Therefore, currently there is a great need for a forum or place in the form of a museum building to provide information related to the development of maritime history in Aceh. The Aceh Maritime Museum is located on Jl. Ulee Lheue Lama Harbor, Meuraxa District, Banda Aceh. The Aceh Maritime Museum aims to store, care for and exhibit historical objects related to the sea and is also a place for recreation and education which is expected to arouse the interest of the younger generation in studying Aceh's maritime history. The problem identification is planning a functional, structural and aesthetic Aceh Maritime Museum as well as applying the Contemporary Architecture theme to the building. This Maritime Museum is categorized as a historical museum managed by the Aceh Provincial government at the level of a National Museum. The application of a contemporary theme to the design results aims to explore a more aesthetic form for the building and translate the designer's ideas to observers in order to increase the attraction of people to visit it. The concept of the building shape was inspired by a typical Acehnese fishing boat which has 4 corners pointing to the four cardinal directions. The analyzes carried out are functional analysis, site analysis and building analysis. The Aceh Maritime Museum has five floors with a single period and has a building area of 10,166 m² on a land area of 20,795 m² (±2 Ha). The available facilities include exhibition space, audio visual, library, auditorium, prayer room, souvenir kiosk, amphitheater and cafe/restaurant with a capacity of 461 people/day. The Aceh Maritime Museum has a KDB of 12,477 m² and a KLB of 49,908 m².